1639 N.J. Laws 18-19 - (:unkn) unknown (My University, 1639)
Ordinance of the Director and Council of New Netherland, Prohibiting the Sale of Firearms . . . to Indians: Prohibited the sale of firearms, and ammunition to "Indians" punishable by death. Informants of violations eligible for monetary reward.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES